Ayurveda Management of Pakshaghata (Hemiplegia) - Acharya, Rajeshwari S; Acharya, Shripathi (International Research Journal of Ayurveda & Yoga, 2020)
Pakshaghata (Hemiplegia) is a neurological disorder where there is loss of sensation and motor deficit in one side of the body . This is due to cerebral arterial thrombosis or cerebral haemorrhage followed by infarction and oedema of brain tissue following ischemia of brain. Clinical features include loss of speech, sensory deficit, motor deficit in the affected side, inability to walk freely and ataxia. After the acute condition, i.e., usually after 7 days, Ayurvedic treatment can be started which gives better results in these patients. In most of the patients, there will be partial or complete motor recovery after 30 days of Ayurvedic treatment. Some patients require prolong treatment for the recovery. Some patients do not recover from the disease. The present paper highlights about the role of Ayurveda management in Pakshaghata (Hemiplegia).